The Impact of 2020 Low Traffic Neighbourhoods on Levels of Car/Van Driving among Residents: Findings from Lambeth, London, UK - Anna Goodman; Anthony A. Laverty; Jamie Furlong; Rachel Aldred (Findings)
We examined how residents' driving changed after the implementation of low traffic neighbourhoods (LTNs) in Lambeth, London. We used postcode plus numberplate data from controlled parking zones, matched to annual MOT records. From 2018-2020 ('pre') to 2021-2023 ('post'), mean past-year driving decreased by 0.7km/day among residents living inside the new LTNs and increased by 0.6km/day among residents in control areas elsewhere in Lambeth. This represents a difference-in-differences decrease of 1.3km/day (95% confidence interval 0.3 to 2.4) in LTN versus control areas, or a 6.4% relative decrease. Our findings suggest that residents started driving less once their area became an LTN.